DAMPAK PERKEMBANGAN SENTRA INDUSTRI TAHU TEMPE DI KELURAHAN ABIAN TUBUH BARU TERHADAP KONDISI LINGKUNGAN - Wiwit Bayu Adi; Agum Muladi; Ahmad Kutbi Rais; Mustiana Mustiana; Joni Safaat Adiansyah (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
Abian Tubuh Baru Village is an industrial center for tofu and tempeh making in Mataram City based on the 2011-2031 Regional Spatial Plan (RTRW). From this potential, it actually causes an impact, namely the pollution of tofu and tempeh waste on the environment. The purpose of this study was to determine the impact of the development of the tofu and tempeh industry in Abian Tubuh Baru Village on environmental conditions and to find out the strategies that had been applied to overcome the impacts caused by industrial development. This type of research is qualitative, the approach method used is DPSIR and Stakeholders. The results show that the development of tofu and tempeh industrial centers has an impact on environmental conditions, such as river pollution, air pollution due to odors generated from waste and noise generated from grinding machines, thus affecting the comfort level of the surrounding community. Meanwhile, the strategy to overcome the impacts that have existed so far has not been running effectively.